Multi-satellite cooperative beam hopping resource allocation based on interference perception - Jinlong HU; Jihong LIU; Yiqing ZHOU; Huan CAO; Zifan LIU; Jiawei ZHAO; Jinhong YUAN (Dianxin kexue)
Beam hopping (BH) technology is one of effective ways to solve limitation of beam resources and enhance the system coverage ability of low earth orbit (LEO) satellite systems.Existing research typically considers beam hopping resource allocation for a single LEO satellite, however, the actual LEO system is covered by multiple satellites in multiple orbits, and existing research ignores beam interference between satellites, which can easily lead to a decrease in system throughput and service quality.To address these issues, this paper designs an interference aware cooperative resource allocation for LEO with beam hopping (IARA-BH), aiming to maximize the beam service satisfaction (BSS).A BH resource allocation scheme by multi satellite interference coordination based on simulated annealing algorithm (MSIC-SAA) is proposed to solve the optimization problem.Simulation experiments show that compared to beam hopping resource allocation schemes that only consider a single satellite, the BSS of the MSIC-SAA algorithm has been improved by 47.24%, the average signal to interference noise ratio (SINR) has been improved by 27.40%, and the system throughput has been improved by 22.92%.